The insecticidal effect of the botanical insecticide chlorogenic acid on Mythimna separata (Walker) is related to changes in MsCYP450 gene expression - Lin, Dong-jiang; Fang, Yong; Li, Ling-yun; Zhang, Li-zhao; Gao, San-ji; Wang, Ran; Wang, Jin-da (Frontiers in Plant Science, 2022)
The oriental armyworm Mythimna separata (Walker) (Lepidoptera: Noctuidae) can feed on the leaves of many crops, resulting in vast areas of damage and severe losses. Therefore, this insect has become a significant agricultural pest in north Asia. In this study, we fed 3rd instar larvae with artificial diets containing different concentrations of chlorogenic acid and found a significant lethal effect and the mortality increased with increasing chlorogenic acid concentration. Next, we measured the sublethal effect of chlorogenic acid at LC20 on the growth and development of M. separata larvae. The durations of the 4th and 5th instar were longer than those of the control group (prolonged by 0.8 and 0.6 days, respectively), and the 6th instar was shorter (by 1.1 days). The total survival rate, pupation rate, eclosion rate, sex ratio, and oviposition amount in the LC20 chlorogenic acid-treated group were significantly lower those in the control group. Furthermore, transcriptome analysis of 3rd instar larvae fed various concentrations of chlorogenic acid revealed that several MsCYP450 genes were significantly up-regulated, and this finding was further validated by qRT-PCR. In addition, various concentrations of chlorogenic acid and different treatment times significantly affected the enzyme activity of CYP450 in 3rd instar larvae. Importantly, dietary ingestion of dsMsCYP450 significantly reduced the mRNA level of MsCYP450 genes and increased mortality in the presence of chlorogenic acid. Our results revealed that MsCYP6B6, MsCYP321A7, and MsCYP6B7-like play an essential role in the detoxification of chlorogenic acid by M. separata. This study provides evidence of control effect by botanical insecticide chlorogenic acid on M. separata, and potential detoxification mechanism mediated by P450 of botanical insecticide in arthropods.